Research Preparedness Paves the Way to Respond to Pandemic H1N1 2009 Influenza Virus. Issue 3 (2009) - French, Michelle B; Loeb, Mark B; Richardson, Carol; Singh, Bhagirath
Abstract : The international community has been preparing for an influenza pandemic because of the threat posed by H5N1 avian influenza. Over the past several years, Canada has dedicated funding to boost capacity for research, and public health and health care system readiness and response in the event of a pandemic. The current H1N1/09 influenza pandemic is now testing our readiness. From a research perspective, the present commentary discusses how have we prepared, along with the research gaps. We conclude that: sources of pandemics are not always predictable; investment in the past few years has paid off in a rapid response to pandemic H1N1/09 virus in Canada; and research to meet the challenges of infectious diseases has to be done on an ongoing long-term basis, and its funding has to be flexible, available and predictable to maintain capacity and expertise. In addition, new vaccine technologies are needed to develop and produce vaccines for public health emergencies in a timely fashion.